دور التحول الديموغرافي في تغيّر التركيب العمري للسكان في سورية - الرفاعي, عبد الهادي ممدوح; شمعون, هنادي; صقر, مهند شفيق (Latakia University Journal - Economic and Legal Sciences Series, 2014)
إنّ الاتجاهات الديموغرافية التي سادت في المجتمع السوري في القرن الماضي, كالانخفاض في معدلات الوفيات وزيادة عدد السنوات لتوقع الحياة عند الولادة, وما يعقبه من انخفاض في معدلات الولادات العالية أدّى إلى انخفاض معدّل النمو السكاني, لقد ساهمت كل هذه التغيرات في تغيّر نسب الفئات العمرية المطولة (الأطفال والشباب والشيوخ), ليزيد هذا التغيّر في زيادة أعداد الوافدين إلى سوق العمل. يرصد هذا البحث دور التحوّل الديموغرافي في التغيرات التي تطرأ على التركيب العمري للمجتمع السوري وتحديد المرحلة التي يختبرها بداية الألفية الثالثة, بالاعتماد على بيانات حول معدّلات الولادات والوفيات ونسب السكان ضمن الفئات العمرية المطولة في سورية مستندين بذلك إلى نتائج التعدادات العامة للسكان. أهم النتائج: - بدأ تحوّل التركيب العمري في سورية منذ منتصف القرن العشرين. - ارتفع معدّل نمو فئة السكان في سن العمل]15-64[سنة من (49%) من مجموع السكان عام(1960) إلى (52.2%) في العام (1994), لتصل إلى (57.2%)عام (2004). - دخلت سورية, بداية الألفية الجديدة, في نهاية المرحلة الثانية وبداية المرحلة الثالثة من مراحل تحوّل التركيب العمري والتي تتميّز بتوسّع أعداد السكان في العمر المتوسّط. The demographictrendsthat dominatedin the Syriansocietyin the last century, As the declineinmortality rates, And the rapid rise of life expectancy at birth, And subsequent decline in the birth rate high Which in turn reduced the rate of population growth, which contributed to the change ratios lengthy age groups(children and young people and the elderly),This change contributed to increase the number of arrivals to the labor market. This search monitors ​​the role of demographic transition in changes in the Age Structural Transition Syrian society And determine the phase experienced by the beginning of the third millennium, Relying on data on birth and death rates and the percentage of the population within the age groups lengthy in Syria so dependent to the results of the general census of the population. the most important results: -theAgeStructural Transition in Syria Started since the mid-twentieth century. -The growth rate rose class working-age population[15-64]year from (49%) of the total population (1960)to (52.2%) in the year (1994), to reach (57.2%) (2004). - Syria entered, the beginning of the new millennium, at the end of the second phaseAnd the beginning of the third stage of Shift the and characterized by the expansion of the number of people in middle age